Meningkatkan Budaya Kuliner Lemang Di Era Society 5.0 - Esis Melisa; Lidya Melia Sari; Diratu Agnes Fitria; Tata Sutabri (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
The Society 5.0 era reflects the world's transition towards a society that integrates digital technology with everyday life. In this context, traditional culinary delights, such as lemang, have the potential to evolve and maintain their relevance amidst changing times. Lemang, a traditional rice-based food prepared by steaming it in bamboo sticks, has become an inseparable part of the culinary heritage of people in several Southeast Asian countries. However, with technological developments and shifts in people's consumption patterns, there is a tendency to ignore traditional culinary delights such as lemang. Therefore, it is important to implement strategies that can promote lemang so that they remain in demand in the Society 5.0 era. Integration of digital technology in the production, distribution and promotion processes of lemang can be a solution. Using social media platforms to promote the uniqueness and deliciousness of lemang, as well as bridging traditional craftsmen with a wider market through e-commerce are some ways to introduce lemang to a new generation. Additionally, innovation in recipes and presentation, without losing its traditional essence, can also be an interesting approach. By combining traditional values and innovation in the Society 5.0 era, lemang will not only survive, but will also increasingly develop and be accepted in the hearts of global society. Culinary is an important aspect of human culture that continues to develop along with the times. The Society 5.0 era, which is marked by the integration of digital technology in everyday life, provides new opportunities and challenges in preserving and improving traditional culinary culture such as lemang. Lemang is a traditional food from Indonesia, Malaysia and several other Southeast Asian countries made from sticky rice cooked in bamboo. This study aims to explain how technology and innovation can be used to improve Lemang culinary culture in the context of the Society 5.0 Era.